At home in the kitchen : simple recipes from a chef's night off - Kinch, David, 1961- (Ten Speed Press, 2021)
When David Kinch isn<U+2019>t working at one of his restaurants, he cooks in his strawberry-colored bungalow<U+2014>affectionately known as the Pink Palace<U+2014>where he lives on the Northern California coast. A casual meal might include a rustic pasta made with cans from the pantry, a simple roasted chicken, or too many oysters to count. In At Home in the Kitchen, you<U+2019>ll find David<U+2019>s ready-for-anything Mother-Sauce Mayo, a revelatory Guacamole with Pomegranate, the best make-ahead Grilled Cheese, and everything you want to eat for dinner tonight: Onion & Brioche Soup, Brussels Sprouts with Cider & Goat Cheese, Penne with a Walnut Sauce, Jambalaya New Orleans Style, Oven-Roasted Potatoes with Cod, Whole Roast Cauliflower with Capers & Egg, and much more. Photographed on location in the coastal town of Santa Cruz, where David surfs, sails, and entertains, this laid-back cookbook is packed with go-to recipes, songs to listen to while cooking, and a few classic cocktails (rhum punch, daiquiris, sangria, margaritas!) to set a cheerful mood. And while each recipe has no more than a few key ingredients, David<U+2019>s clever techniques, subtle twists, and fresh flavor combinations guarantee delicious<U+2014>and impressive!<U+2014>results in no time at all.